The The Effect of Tea Tree Oil (Melaleuca alternifolia) on Candida albicans Counts on Heat-Cured Acrylic Resin and 3D-Printed Acrylic Denture Base Materials - Wennie Fransisca; Fitri Dona Siregar; Rana Raihana Ritonga; Ramijat Ryachudu Sitorus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Suboptimal cleaning of dentures can increase the overgrowth of Candida albicans, which can cause denture stomatitis. Therefore, it is important to maintain denture hygiene with effective and safe cleaning agents. One natural ingredient that has the potential to be used as a denture cleaner is Tea Tree Oil (Melaleuca alternifolia), which is known to have antifungal activity. This study aims to compare the effectiveness of Tea Tree Oil immersion at concentrations of 0.25%, 0.5%, and 1% against 0.5% sodium hypochlorite in inhibiting the growth of Candida albicans on heat-cured acrylic resin plates and 3D-printed acrylic resin. This study is an experimental laboratory study with a post-test only control group design. The research population consisted of pure culture isolates of Candida albicans ATCC 10231. The research samples consisted of heat-polymerized acrylic resin plates and 3D-printed acrylic resin plates measuring 10×10×2 mm, with 5 samples in each treatment group that were immersed for 8 hours. The number of Candida albicans colonies was counted using the plate count method and calculated with a colony counter. The data were analyzed using the Kruskal-Wallis test, followed by the Mann-Whitney test. The results showed that there was a difference in the effectiveness of Tea Tree Oil immersion at various concentrations compared to 0.5% sodium hypochlorite and distilled water against the growth of Candida albicans. Tea Tree Oil concentrations